Transmembrane voltage potential is an essential cellular parameter for the detection and control of tumor development in a Xenopus model - Brook T. Chernet (Disease Models & Mechanisms, 2013)
SUMMARY Understanding mechanisms that orchestrate cell behavior into appropriately patterned tissues and organs within the organism is an essential element of preventing, detecting and treating cancer. Bioelectric signals (resting transmembrane voltage potential gradients in all cells) underlie an important and broadly conserved set of control mechanisms that regulate pattern formation. We tested the role of transmembrane potential in tumorigenesis mediated by canonical oncogenes in Xenopus laevis. Depolarized membrane potential (Vmem) was a characteristic of induced tumor-like structures (ITLSs) generated by overexpression of Gli1, KrasG12D, Xrel3 or p53Trp248. This bioelectric signature was also present in precursor ITLS sites. Vmem is a bioelectric marker that reveals ITLSs before they become histologically and morphologically apparent. Moreover, voltage was functionally important: overexpression of hyperpolarizing ion transporters caused a return to normal Vmem and significantly reduced ITLS formation in vivo. To characterize the molecular mechanism by which Vmem change regulates ITLS phenotypes, we performed a suppression screen. Vmem hyperpolarization was transduced into downstream events via Vmem-regulated activity of SLC5A8, a sodium-butyrate exchanger previously implicated in human cancer. These data indicate that butyrate, a histone deacetylase (HDAC) inhibitor, might be responsible for transcriptional events that mediate suppression of ITLSs by hyperpolarization. Vmem is a convenient cellular parameter by which tumors induced by human oncogenes can be detected in vivo and represents a new diagnostic modality. Moreover, control of resting membrane potential is functionally involved in the process by which oncogene-bearing cells depart from normal morphogenesis programs to form tumors. Modulation of Vmem levels is a novel and promising strategy for tumor normalization.